Implementasi Sistem Informasi Manajemen dalam Mendukung Proses Pembelajaran Daring pada Pendidikan Anak Usia Dini - Rani Astria Silvera Harahap; Rahyana Hasibuan (Institut Agama Islam Tribakti Kediri, 2022)
In order to achieve the educational goals that are expected, teaching and learning activities in school institutions will be better if a school institution has an information system that can manage these learning activities. Management information system is a that can help a leader in the form of information in making decisions. Thus, the school institution can provide information with a variety of according to what is needed. Look at the current pandemic and development of information technology especially by educational institutions in early childhood education programs (PAUD), learning activities can take place remotely (online) via the internet assisted by parents. That way the learning that is done is more effective and efficient.